Autism-spectrum disorders in adolescence and adulthood: focus on sexuality. Issue 6 (November 2017) - Turner, Daniel; Briken, Peer; Schöttle, Daniel
Abstract : Purpose of review: The combination of the core symptoms, characterizing individuals with autism-spectrum disorder (ASD), can lead to problems in romantic relationships and sexual functioning. The purpose of this article is to review studies on sexuality in individuals with ASD published since January 2016. Recent findings: Individuals with ASD and especially women show a higher diversity in sexual orientation in comparison with the non-ASD population. Furthermore, ASD women are more frequently in a relationship and usually report more previous sexual experiences. Up to now, sexual education programs specifically addressing the needs of the ASD population were scarce, which was criticized by patients, their parents, and caregivers. With the development of the Tackling Teenage Training program, a psychoeducational intervention designed specifically for ASD individuals was introduced, leading to significant improvements in psychosexual functioning and knowledge. Such programs are needed because a considerable rate of problematic sexual behaviors, including public masturbation and paraphilic sexual interests were found in the ASD population. Summary: Just like their typically developing counterparts, individuals with ASD show the whole range of normal-to-problematic sexual behaviors. Improving sexual knowledge could lead to less inappropriate sexual behaviors and could improve sexual health as part of a healthy and satisfying life.